2016
DOI: 10.1016/j.thromres.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Body size measures, hemostatic and inflammatory markers and risk of venous thrombosis: The Longitudinal Investigation of Thromboembolism Etiology

Abstract: Objective Obesity is an important venous thrombosis (VT) risk factor but the reasons for this are unclear. Materials and Methods In a cohort of 20,914 individuals aged 45 and older without prior VT, we calculated the relative risk (RR) of VT over 12.6 years follow-up according to baseline body size measures, and studied whether associations were mediated by biomarkers of hemostasis and inflammation that are related to adiposity. Results Greater levels of all body size measures (weight, height, waist, hip c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 41 publications
5
47
1
Order By: Relevance
“…CRP levels have been directly proportional to the thrombotic load, the extension and volume of thrombus [25]. While some studies did not show a link between CRP levels and a future venous thrombotic event, others demonstrated a significant correlation between high levels of CRP and further development of thromboembolism [1,2,15,24].…”
Section: Crpmentioning
confidence: 99%
See 4 more Smart Citations
“…CRP levels have been directly proportional to the thrombotic load, the extension and volume of thrombus [25]. While some studies did not show a link between CRP levels and a future venous thrombotic event, others demonstrated a significant correlation between high levels of CRP and further development of thromboembolism [1,2,15,24].…”
Section: Crpmentioning
confidence: 99%
“…While some studies did not show a link between CRP levels and a future venous thrombotic event, others demonstrated a significant correlation between high levels of CRP and further development of thromboembolism [1,2,15,24]. Although previous studies showed that at the moment of diagnosis there are high levels of CRP, it was proven that plasma CRP levels have no utility in infirming or confirming this diagnosis in patients with clinical suspicion of deep vein thrombosis [1,2,18,25]. Nevertheless, CRP plays a role in assessing the mortality risk and early complications [24,25].…”
Section: Crpmentioning
confidence: 99%
See 3 more Smart Citations